The Effect of Flow Characteristic on Generic Shape of an Automotive Side Mirror - Mat Nuri @ Md Din, Nur Rashid; Mansor, Dr Shuhaimi; Abd Rahman, Muhammad Riza (2010)
In this paper, an aerodynamics effect of a simple side mirror geometry with different foot height and foot width is discussed. The numerical simulation is done by using Fluent software with two solvers which are k-epsilon standard and realizable turbulence models. The results obtained are discussed in term of velocity magnitude and pressure coefficient at side mirror surface and side window. Turbulent intensity along the horizontal air flow direction from the center of side mirror surface also has been discussed. With all these results, the best design of simple side mirror geometry has been proposed.